Multiscale modelling of drug-polymer nanoparticle assembly identifies parameters influencing drug encapsulation efficiency - Mackenzie, Robert; Booth, Jonathan; Alexander, Cameron; Garnett, Martin; Laughton, Charles A. (American Chemical Society, 2015)
Using a multiscale (dual resolution) approach combining an atomistic (GROMOS96) and coarse-grain (MARTINI) force field, we have been able to simulate the process of drug-polymer nanoparticle assembly by nanoprecipitation from mixed solvents. Here we present the development and application of this method to the interaction of three poly(glycerol adipate) polymer variants with the anti-cancer drug dexamethasone phosphate. Differences in encapsulation efficiency and drug loading between the polymers are in agreement with the experimental trend. Reference atomistic simulations at key points along the predicted aggregation pathway support the accuracy of the much more compute-efficient multiscale methodology.